Evaluasi Kebijakan Penanggulangan HIV/AIDS di Kota Semarang - Elsia Putri Hutabarat; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
HIV disease has complexity and differences in the calculation of the number of findings of cases with other diseases. Supposedly like an iceberg, the task of the government is to find exposure to cases that are not visible from the surface, such as at risk populations. The more cases of findings, the better the performance of the government. This statement is in line with the increasing number of findings and is the proof of the success of Regional Regulation No.4 of 2013 concerning HIV / AIDS Prevention in the City of Semarang in revealing the iceberg tragedy. This research is a descriptive qualitative study that aims to describe and analyze the results of policy achievements and related factors that hinder the achievement of Regional Regulation No.4 of 2013. It is hoped that this policy can be a model for other policies in terms of their effectiveness, efficiency and responsiveness. The results of the study indicate that the level of HIV / AIDS diagnosis, fulfillment of information and health services, and the quality of human resources achieved have been effective. Policy efficiency can be seen from the implementation of KTHIV and ARVs, government cooperation with NGOs, and routine meetings. Responsiveness is reflected in people's participation and enthusiasm, client’s satisfaction of service, and enthusiasm for HR in attending regular meetings. There are several inhibiting factors, namely communication, resources, and disposition. The suggestions in this study are to hold a cooperation contract of Working Group as a form of firmness on absence at coordination meetings; the need to avoid inequal service quality by gathering all health care workers; and the provision of service to address complaints, critics, and suggestions from the community to improve countermeasure services by becoming more responsive to the community needs.